ChemInform Abstract: Total Syntheses of Isowondonins Based on a Biosynthetic Pathway. Issue 44 (13th October 2016) - Yu, Shuai; Li, Feng; Jeon, Hongjun; Lee, Seokwoo; Shin, Jongheon; Kim, Sanghee
Abstract: The first total syntheses of the bis(dihydroxystyrenyl)imidazole marine alkaloids isowondonin A (I) and isowondonin B (II) are completed.